Analisis perbandingan kinerja manajemen dengan menggunakan metode RGEC (risk profile, good corporate governance, earning, capital) pada bank umum BUMN yang terdaftar pada Bursa Efek Indonesia tahun 2022 - Yolda Juliandri Patasik; Harijanto Saibjono; Meily Y. B. Kalalo (Yayasan Widyantara Nawasena Raharja, 2023)
Banking is a sector that plays an important role in society, especially in economic development. Bank Indonesia as the bank that supervises banks in Indonesia issued PBI No. 13/1/PBI/2011 regarding the Assessment of the Health Level of Commercial Banks using the RGEC method (Risk Profile, Good Corporate Governance, Earning, Capital). This study aims to compare the management performance of state-owned commercial banks using the RGEC method. The research method used in this research is a descriptive method with a qualitative approach and the data used is secondary data obtained from the published financial statements of BUMN commercial banks. The results showed that the NPL, LDR, and GCG ratios of the management performance of BUMN commercial banks were not much different from the criteria of very healthy and healthy. However, the ROA and BOPO ratios show differences in management performance, where there is one bank that is in the fairly healthy criteria and the other three banks are in the healthy criteria. The CAR ratio of all state-owned commercial banks is very healthy.